(untitled) (The Peerian Journal, 2025)
This article analyzes the role of stress correction in restoring the psychological health of people with disabilities. The impact of stress on the health of this category of people, their negative impact on social and psychological adaptation, and the mechanisms for overcoming them through corrective approaches are considered. The significance of modern forms of psychological assistance, including relaxation methods, art therapy, cognitivebehavioral therapy, and group psychocorrectional sessions, is revealed. The article also includes practical recommendations aimed at restoring the mental stability of citizens with disabilities through stress correction.a